Revisioning transpersonal theory : a participatory vision of human spirituality - Ferrer, Jorge N. (Jorge Noguera), 1968- (SUNY series in transpersonal and humanistic psychology., 2002)
"Jorge N. Ferrer deconstructs and reconstructs the entire transpersonal project, articulating a more sophisticated, pluralistic, and spiritually grounded transpersonal theory. He brings recent ideas in epistemology and the philosophy of science to bear upon core issues in the psychology and philosophy of religion. The book's first half (Deconstruction) describes the nature and origins of the prevailing vision that has guided transpersonal scholarship so far, and identifies some of its main conceptual and practical limitations: subtle Cartesianism, spiritual narcissism, intrasubjective empiticism, and reductionistics universalism. In the second half of the book (Reconstruction). Ferrer suggests a way of reconceiving transpersonal ideas without these limitations - a participatory vision of human spirituality one which not only places transpersonal studies in greater alignment with the values of the spiritual quest, but also discloses a rich variety of spiritual liberations, spiritual worlds and even ultimate realities."--Jacket